2019
DOI: 10.1111/cag.12519
|View full text |Cite
|
Sign up to set email alerts
|

Food for naught: Using the theory of planned behaviour to better understand household food wasting behaviour

Abstract: Key MessagesRespondent households threw out food 4.77 times/week and 5.89 food portions/week. Reducing monetary impact of food waste was identified as the most selected food waste reduction motivator.Perceived behavioural control was identified as an important determinant of food wasting behaviour.To better understand food wasting behaviour, the theory of planned behaviour was used to inform the development of a survey which was administered to households in London, Ontario, Canada. Respondent households (n ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 37 publications
7
67
2
1
Order By: Relevance
“…FWB in this study was measured by shopping routines, food preparation, and self-reported food waste, and thus, these socio-demographic factors predict the likelihood of respondents to buy and cook too much food, as well as throw out food. Similar to previous studies, socio-demographics only explained little of the variance of FWB in both countries [12,18]. Rather, attitudes, values, and other psychographic variables have been previously shown to be more closely related to behavioral outcomes [6,17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…FWB in this study was measured by shopping routines, food preparation, and self-reported food waste, and thus, these socio-demographic factors predict the likelihood of respondents to buy and cook too much food, as well as throw out food. Similar to previous studies, socio-demographics only explained little of the variance of FWB in both countries [12,18]. Rather, attitudes, values, and other psychographic variables have been previously shown to be more closely related to behavioral outcomes [6,17].…”
Section: Discussionsupporting
confidence: 82%
“…However, evidence suggests that socio-demographic characteristics have weak predictive power of food waste [10,17]. Previous studies have found socio-demographics to explain only 7-13% of the variance regarding intention to reduce and perceived behavioral control to avoid household food waste [12,18]. Despite the limited predictive power, correlations between age, sex, employment status, income, household size and composition, and amount of food wastes have been found, but the strength and direction of the relationships vary between studies [7].…”
Section: Introductionmentioning
confidence: 99%
“…This compares with 8.9 to 9.9 kg/household/week of pre-intervention garbage for London, Ontario households, of which 2.5 to 3.4 kg/household/ week was total food waste. This food waste range compares favorably with the estimated 2.6 kg/household/week of total food waste generated by southern Ontario households without access to a program to remove source-separated food wastes (van der Werf et al, 2018). As expected, this is higher than for households with such a program (i.e., diversion of mostly food waste to large-scale composting or anaerobic digestion facilities), which on average disposed 2.3 kg/household/week of food waste (van der Werf et al, 2018).…”
Section: Comparison With Other Similar Studiesmentioning
confidence: 77%
“…Food waste reduction motivators. The strongest potential food waste reduction motivators appear to be saving money (Abeliotis, 2014;Porpino, 2016;Tucker & Farrelly, 2016) and moral values (Bolton, 2012;Graham-Rowe et al, 2014;Neff, 2015;Quested, Marsh, Stunell, & Parry, 2013, van der Werf, Seabrook & Gilliland, 2019. For instance, the financial impacts of purchasing too much food is a driver that can reduce food waste (Graham-Rowe et al, 2014;Quested et al, 2013;Williams et al, 2012).…”
Section: Intervention Development Prerequisitesmentioning
confidence: 99%
See 1 more Smart Citation